The Implementation of the Human Resource Management Function in Improving the Performance of the Special Police of Class IIa Sibolga Prison Requirements - Rio Ari Angga; Muhammad Lathief Ilhamy Nasution; Rahmat Daim Harahap (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Management has existed since humans existed; management is as old as human life. management is as old as human life, why is that, because humans in their daily lives cannot be separated from the principles of management This study aims to determine the Application of the Human Resources Management Function in Improving the Duties of Special Correction Police at the Sibolga City Class IIA Correctional Institution. Human resources have a huge role in an organization. Human resource management should be viewed as an extension of the traditional view of managing people effectively and to manage people effectively and to do so requires knowledge of human behavior and the ability to manage it. about human behavior and the ability to manage it. So important position of human resources so that it becomes the achievement or failure of an organization. The results of this study are expected to be input for the government in this case the Sibolga city class IIA correctional institution in order to improve the duties of the special correctional police so as to properly foster the prisoners.